Collaborative Online Learning Design Through Lesson Study Activities for Mathematics Prospective Teacher - Isnawan, Muhamad Galang; Santosa, Farah Heniati; Nurafifah, Luthfiyati; Gunadi, Farid; Mulyana, Diki (Universitas Wiralodra, 2024)
The aim of the research was to develop a collaborative online learning design for integral calculus courses through lesson study activities. The study employed didactical design research as the research design. Participants in the research consisted of 19 students (aged 19–22 years, 18 women) from two private universities in Indonesia. The researcher served as the main instrument in the study, utilizing several additional instruments, such as collaborative online learning design, presentation slides, and documentation studies. The data were analyzed using qualitative data analysis. The research revealed that collaborative online learning design through lesson study activities helped prospective mathematics teachers understand concepts related to integral calculus, especially definite integrals and the substitution method. This was because the collaborative online learning design used learning videos as a means for students to understand the concept of integral calculus. Apart from that, the collaborative online learning design also facilitated students’ understanding of this concept more deeply.